Relationship Analysis of Risk Factors Concerning the Incidence of Pulmonary Tuberculosis in Children at Panti Abdi Dharma Hospital, Cirebon, Indonesia - Pratama, Annisa Shintya; Nisaa, Defa Rahmatun; Ruhyana, Nanang (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Tuberculosis (TB) is an infectious disease caused by the Mycobacterium tuberculosis germ. The germs are spread from people with TB through the air. Nearly a quarter of the world’s population is infected with Mycobacterium tuberculosis germs and 11% are children. Aims: To analyze the association of risk factors that most influence the incidence of pulmonary tuberculosis in children at Panti Abdi Dharma Hospital, Cirebon City in 2024. Methods: Using a cross sectional analytical observational approach, systematic sampling technique on 138 respondents using bivariate analysis (chi-square) and multivariate analysis (logistic regression). Results: The results showed that risk factors associated with the incidence of tuberculosis in children were age (P-value 0.002), gender (P-value 0.027), father's education (P-value 0.032) and parents' socioeconomic status (P-value 0.001). The risk factor that most influenced the incidence of tuberculosis was parents' socioeconomic status (Exp(B) value 3.798). Conclusion: In the 10 risk factors studied, 4 risk factors were found to have an association with the incidence of tuberculosis in children, namely child age, child gender, father's education, and parents' socioeconomic status. The most influential risk factor in this study was parents' socioeconomic status.